РАДИОЭКОЛОГИЧЕСКИЙ ДИАПАЗОН ПРОИЗРАСТАНИЯ РАСТЕНИЙ НА ОПЫТНО- ЭКСПЕРИМЕНТАЛЬНОЙ ПЛОЩАДКЕ «БАЛАПАН» БЫВШЕГО СЕМИПАЛАТИНСКОГО ИСПЫТАТЕЛЬНОГО ПОЛИГОНА (Experimental biology, 2011)
The paper provides an analysis of the identified group of plants with different resistance to radiation contamination. As a result of studies identified species recorded in the "dangerous" and "very dangerous" doses, which can be recommended as the rehabilitation of the territory fitoremidiantov Semipalatinsk test site.
Keywords: "dangerous"; "very dangerous"